Estudo de adaptação transcultural do Genos Emotional Intelligence Inventory (GENOS EI) para o contexto organizacional brasileiro - Pacheco, Orjana de Oliveira (Universidade Federal de São Carlos, 2023)
The Emotional Intelligence (EI) has been pointed as an important competence to several contexts, among them, the organizational. However, related to the scientific investigations, it´s fundamental to dispose of quality instruments to the EI measure. Due to the scarcity of the IE instruments to the Brazilian organizational context, the current research aimed to realize transcultural adaptation studies and validity evidence of the self-report foreign instrument- Genos Emotional intelligence inventory (GENOS EI) to the Brazilian laboral context. To this purpose, the research took in consideration 589 workers and was subdivided by in three studies- Articles. The first aimed at the linguistic- cultural adaptation process and GENOS EI semantic in six stages. As a result, it was got the context validity evidence of the adapted instrument to the Brazilian laboral context. The second aimed the search of the validity evidences of the internal structure. The results of this second article pointed the GENOS-EI-Br factorial organization adapted different from the original structure, once out of seven factors, it was identified four. This new configuration eliminated thirty items out of seventy from the original, from the established criteria on and vigorous indicators and applied to the Exploratory Factorial Analysis (EFA) and, later on confirmed by the Confirmatory Factorial Analysis (AFC). Considering the instrument as a whole, the general factor presented indexes of Cronbach Alpha (α= 0.92; IC 95% [ 0,91-0,93]) and Mc Donald omega (ω =0,92;IC 95%[ 0,91-o,93) and the factors accuracy estimation was from 0,52 to 0,83 and the general factor of the 0,85. Finally, the third article searched for the validity evidences related to the GENOS-EI-Br adapted to the Brazilian organizational context based on the report with other variable of the Laboral ambit: self-efficiency, personality and work satisfaction. The obtained results of the correctional analysis demonstrated a positive correlation, meaningful and moderated between the GENOS-EI-Br and the self-efficiency, as well as among three out of the four factors of the GENOS-EI-Br and the work satisfaction. There was also a positive correlation, meaningful and low of GENOS-EI-Br with four out of five personality factors, exhausting the neuroticism factor. Through regression analyses, it was possible to identify that only the first factor, self-management and emotional self-control (AAE), of GENOS-EI-Br, predict in a meaningful way, the levels of work satisfaction and self-efficiency and the personality factors predict the EI in the collected sample. The three studies indicate positive results of the validity evidence to the GENOS-EI-Br adapted to the Brazilian laboral context.
Cross-cultural adaptation study of the genos emotional intelligence inventory (GENOS EI) to the brazilian organizational context
Keywords: Inteligência emocional; Contexto organizacional; Adaptação de instrumento; GENOS EI; Adaptação transcultural; Emotional intelligence; Organizational context; Instrument adaptation; Transcultural adaptation; CIENCIAS HUMANAS::PSICOLOGIA